A Review on Working Load and Burnout Toward Patient Safety in Radiology Unit - Cici Pratama; Setya Haksama; Stefani Widodo (Universitas Muhammadiyah Purwokerto, 2026)
Burnout is prevalent among radiology professionals and has been consistently linked to increased self-reported medical errors in various healthcare settings. However, direct evidence connecting burnout measured by the Maslach Burnout Inventory (MBI) to diagnostic errors in radiology image interpretation is lacking. This systematic review highlights an inferential gap due to the absence of studies simultaneously assessing MBI-measured burnout and objectively measured diagnostic errors in radiology. The strongest available evidence from prospective longitudinal studies in non-radiology populations demonstrates a bidirectional, dose-dependent association between burnout domains and perceived medical errors. Given the cognitive demands of radiological interpretation and the documented impact of burnout on cognitive functions, future research should directly evaluate this relationship within radiology professionals, incorporating relevant contextual moderators to inform targeted interventions aimed at improving patient safety.